Heterotrophic Potentials and Hydrocarbon Biodegradation Potentials of Sediment Microorganisms Within the Athabasca Oil Sands Deposit - Wyndham, R. C. (1981)
Techniques for the enumeration and the determination of the potential activity of disturbed sediment mixed populations at control sites and sites within the Athabasca oil sands formation were applied to August and December samples. These techniques included the determination of general heterotrophic potential for the assimilation and respiration of glutamate, which indicated no oil sand-related changes in the sediments but which indicated a significant seasonal change. Enumeration by epifluorescence direct counts, oil sand hydrocarbon plate counts, and most-probable-number determinations of [(14)C]hexadecane and [(14)C]-naphthalene degraders indicated that only the plate count was sensitive to increased numbers of oil sand-related hydrocarbon-oxidizing microorganisms within the oil sands deposit. Unlike the most probable number determinations of [(14)C]hexadecane and [(14)C]naphthalene degraders, however, the biodegradation potential results of these substrates indicated a significant increase in activity at oil sands sites. These biodegradation potentials also showed a marked seasonal fluctuation. Although the biodegradation potentials and the endogenous hydrocarbon plate counts indicated an oil sand-adapted mixed sediment population, the results of these techniques did not correlate well with the concentrations of bituminous hydrocarbons in the sediments. The results suggest that a general capability for hydrocarbon oxidation exists in the Athabasca River system and that this capability is enhanced within the natural bounds of the Athabasca oil sands.